2011
DOI: 10.1177/0143034311402916
|View full text |Cite
|
Sign up to set email alerts
|

Response to trauma in children: An examination of effective intervention and post-traumatic growth

Abstract: It is clear that exposure to traumatic events is not uncommon in childhood and adolescence and psychologists working in schools should have some training in meeting the needs of this segment of the population. This manuscript summarizes the incidence of trauma in children worldwide and then discusses interventions for trauma (TraumaFocused Cognitive Behavior Therapy & Cognitive Behavioral Intervention for Trauma in Schools) which have been empirically validated for use with children and/or adolescents. A summa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 45 publications
3
14
0
Order By: Relevance
“…The findings showed statistically higher levels of posttraumatic growth among youth participating in camp as compared to those who did not take part in camp. The results coincide with previous findings in pre-experimental studies examining PTG among youth that had experienced trauma (Glad et al, 2013;Little et al, 2011). PTSD symptoms decreased, but not to a statistically significant degree.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The findings showed statistically higher levels of posttraumatic growth among youth participating in camp as compared to those who did not take part in camp. The results coincide with previous findings in pre-experimental studies examining PTG among youth that had experienced trauma (Glad et al, 2013;Little et al, 2011). PTSD symptoms decreased, but not to a statistically significant degree.…”
Section: Discussionsupporting
confidence: 90%
“…Also, although there were clinically significant posttraumatic stress reactions displayed among all of the participants, PTSD was not found to have a substantial relationship with levels of PTG. Little, Akin-Little, and Somerville (2011) studied the efficacy of Project Fleur-de-lis, a program designed to help children in the aftermath of Hurricane Katrina. The project used a three-tier method, moving from least intensive to most intensive intervention: Classroom-Camp-Community-Culture Based Intervention (CBI), Trauma-Focused Cognitive Behavior Therapy (TF-CBT), and Cognitive Behavioral Intervention for Trauma in Schools (CBITS).…”
Section: Outcome Studiesmentioning
confidence: 99%
“…A few qualitative studies have suggested that some children who lost parents to AIDS experienced personal growth, emotional maturity, and sense of independence (Murphy, Roberts, & Herbeck, 2013). These findings are consistent with the phenomenon of post-traumatic growth, which refers to awareness of new possibilities, appreciation of life, and spiritual change (Little, Akin-Little, & Somerville, 2011). In a qualitative examination of long-term effects of parental cancer in childhood through retrospective interviews with adults, about 44% of participants spontaneously reported post-traumatic growth (Wong, Cavanaugh, MacLeamy, Sojourner-Nelson, & Koopman, 2009).…”
Section: Resilience Processsupporting
confidence: 88%
“…This chronic stress may function differently than acute stress, such as that experienced during natural disasters, although notably both types of experiences may be related to lower educational outcomes or opportunities for post-traumatic growth (see Little & Akin-Little, 2011). Recent work on trauma experienced by children, naturally-caused or man-made, and their ability to rebound (or not) from those forces, merits consideration (Little, Akin-Little & Somerville, 2011; Nastasi, Overstreet, & Summersville, 2011). Future research could examine which aspects of intervention programs designed for wide-spread natural destruction response are relevant to contexts of historic and ongoing threat.…”
Section: Discussionmentioning
confidence: 99%